Safeguarding freshwater biodiversity and resilient social-ecological systems in uncertain futures - Arthington, Angela H. (Frontiers in Environmental Science, 2025)
Freshwater ecosystems and their diverse plant and animal communities are neglected, under-appreciated and threatened by the multiple interacting stressors of the Anthropocene era. Climate change is the most ominous threat on the horizon and freshwater ecosystems are particularly vulnerable. Climate change, multiple stressor syndromes and other uncertainties challenge freshwater restoration and conservation. This perspective presents a brief summary of major gaps in knowledge, governance and implementation that inhibit efforts to protect and restore freshwater biodiversity and offers guidance to address major gaps. The mission for freshwater science over the next decade is to leverage robust scientific knowledge, governance, funding and policy to inform freshwater restoration and conservation action plans (e.g., the Emergency Recovery Plan, GBF 30 × 30, SDGs, The Freshwater Challenge), and even to exceed their present targets, while simultaneously safeguarding resilient social-ecological systems and human wellbeing under climatic and other uncertainties.